+0  
 
0
52
1
avatar

solve the following equation

 

 Apr 11, 2020
 #1
avatar+20961 
0

Solve:  (3x + 1) / (3x + 2)  =  (x + 2) / (x - 5)

                  (3x + 1)(x - 5)  =  (x + 2)(3x + 2)                        (cross multiply)

              3x2 + x - 15x - 5  =  3x2 + 6x + 2x + 4                    (multiply out)

                           -14x - 5  =  8x + 4                                     (simplify)

                                 -22x  =  9

                                      x  =  -9/22

 Apr 11, 2020

23 Online Users

avatar